Transcriptomic analysis reveals TME-mediated macrophage IFIT1 upregulation and CX3CR1 suppression drive osteosarcoma progression - Wang, Keyi; He, Huanyang; Liang, Jiamin; Su, Yuangang; Zhao, Jinmin; Liu, Qian (Frontiers in Oncology, 2025)
IntroductionOsteosarcoma (OS) is one of the most common bone tumors with an unsatisfactory prognosis for patients. Due to the stagnation in conventional treatments, researchers are exploring therapeutic targets from the tumor microenvironment (TME) and tumor-associated macrophages (TAM). Our study investigates how OS TME influences macrophage gene expression, potentially informing OS treatment strategies.MethodsRNA sequencing was performed on bone marrow-derived macrophages (BMMs) cultured with or without K7M2 conditional medium (CM) for 48 h to analyze gene expression changes. Single-cell sequencing and PCR were used to examine the expression levels of IFIT1 and CX3CR1. Their functions were verified through flow cytometry, cloning, wound healing, and transwell assays using IFIT1 protein and CX3CR1 inhibitors.ResultsWe observed changes in the morphology and transcriptome of BMMs exposed to K7M2 CM. Differentially expressed genes (DEGs) exhibited complex interactions and were enriched in multiple functions and pathways. The upregulation of IFIT1 and the downregulation of CX3CR1 were the most representative. Inhibiting CX3CR1 can promote TAM polarization, thereby accelerating the progression of osteosarcoma. Additionally, increasing IFIT1 also promotes osteosarcoma.ConclusionsStimulation of the OS TME can change the gene expression of macrophages. Our findings offer a cellular and molecular reference for future investigations of therapeutic targets of OS.